PSIKOLOGI MEDIA: UNTUK MEMBENTUK KOMUNIKASI POSITIF DI JARINGAN ONLINE - Lusiawati, Ira (UKRI, 2025)
The digital era divides communication entities into two types. First, the type of real communication that occurs in the real world and second, the type of virtual communication that takes place on online networks. If analyzed, there are significant differences between the two types of communication. The difference lies in its dimensions. Communication in the real world emphasizes more on relationships and in the virtual world emphasizes more on the content dimension. Although technology continues to be developed so that the content dimension can resemble the type of communication in the real world, communication through media will not be able to exactly replace communication in the real world. There is a psychological dimension that underlies it and often cannot be expressed in real terms into the media world. However, both play a very important role in forming a positive communication ecosystem. Therefore, to understand the differences between the two, this study was conducted with the aim of understanding the psychological dimensions that cannot be expressed through media methods. The research approach used is a qualitative method to precisely reveal the elements that form media communication with a positive psychological basis. The results of the study prove that communication actions in online networks can lead to positive situations with awareness of the effects that will be caused.